Efektivitas Model Pembelajaran Problem Based Learning Pada Pembelajaran Jarak Jauh - Anik Rahayu; Yustika Irfani Lindawati (Indonesian Publication Center, 2021)
Distance Learning is a learning method that is applied during the outbreak of the Covid-19 virus, especially in Indonesia. Problems accompany the application of distance learning so it is necessary to collaborate with other learning models that can direct students to be more active in carrying out learning activities. This writing aims to determine the effectiveness of the application of the problem-based learning model in distance learning. The research location was conducted at SMAN 1 Banjarsari with the research subjects being students of class XI IPS 2. The research method used was survey research with a descriptive approach. The data collection technique was carried out through a questionnaire instrument that was compiled using the google form. Respondents of the study were 30 students who were determined by the purposive sampling technique. Data analysis was performed using descriptive statistical techniques where the data were processed and presented in diagrams and then discussed with descriptive narrative. The results of the study found the effectiveness of the problem-based learning model in distance learning, namely 1) increasing students' ability to think critically in problem-solving; 2) improve students' skills in innovation; 3) encourage students to be more active in participating during teaching and learning activities; 4) encourage students' ability to formulate solutions to social problems independently.